Macrophages inhibit Coxiella burnetii by the ACOD1‐itaconate pathway for containment of Q fever. Issue 2 (7th December 2022) - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler‐Tenorio, Elisabeth; Schulze‐Luehrmann, Jan; Mauermeir, Michael; Yang, Kai‐Ting; Hayek, Inaya; et al.
Abstract: Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis‐aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti‐microbial candidate genes, including Acod1 . In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1 −/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1 −/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii . Finally, treatment of infected Acod1 −/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1‐derived itaconate is a key factor in the macrophage‐mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever. Synopsis: The intracellular bacterium Coxiella burnetii causes the anthropozoonotic infection Q fever. Most patients control and resolve infection, but some develop chronic disease. Finding out how macrophages inhibit bacterial replication may explain susceptibility and suggest new therapies. Coxiella burnetii induces expression of the enzyme Aconitate Decarboxylase 1 (ACOD1) in mouse and human macrophages. Acod1 −/− mice and macrophages do not generate the immunometabolite itaconate and fail to control C. burnetii replication in vitro and in vivo . Itaconate directly blocks C. burnetii replication at physiological concentrations. Treatment with itaconate restores control of C. burnetii in macrophages and in mice. Human macrophages generate less itaconate and allow C. burnetii replication, which is inhibited by exogenous itaconate. Abstract : The intracellular bacterium Coxiella burnetii causes the anthropozoonotic infection Q fever. Most patients control and resolve infection, but some develop chronic disease. Finding out how macrophages inhibit bacterial replication may explain susceptibility and suggest new therapies.